Reagentless and sensitive determination of carcinoembryonic antigen based on a stable Prussian blue modified electrode. Issue 63 (16th October 2020) - Lin, Jing; Li, Kunyin; Wang, Meifang; Chen, Xiaohong; Liu, Jiyang; Tang, Hongliang
Abstract : A label-free electrochemical sensor is easily fabricated based on stable and surface-confined Prussian blue for reagentless and sensitive detection of carcinoembryonic antigen. Abstract : Reagentless and sensitive detection of tumor biomarkers using label-free electrochemical immunosensors is highly desirable for early and effective cancer diagnosis. Herein, we present a label-free electrochemical immunoassay platform based on surface-confined Prussian blue (PB) redox probes for sensitive and reagentless determination of carcinoembryonic antigen (CEA). To facilitate the electron transfer of probes and improve sensitivity, Au nanoparticles and PB (Au–PB) are electrochemically co-deposited on a carbon nanotube (CNT) modified glassy carbon electrode (GCE). A polydopamine (pDA) layer is coated on the Au–PB nanocomposite layer in situ as a bifunctional linker. In addition to improving the stability of PB, pDA also provides reducibility for the preparation of gold nanoparticles, which offers an interface for anti-CEA antibody immobilization. The fabricated immunosensor has good stability and is able to reagentlessly detect CEA over a wide range (0.005–50 ng mL −1 ) with high reproducibility. Furthermore, the immunosensor was used for determination of CEA in human serum samples.